Textual Error Analysis on the Use of Simple Present Tense in Writing Descriptive Text - Fadilah Fadilah (ITScience (Information Technology and Science), 2022)
Finding out the frequency, kind, causes, and effects of linguistic failures is the process of error analysis. This study aims to pinpoint students' mistakes when using the simple present tense to write a descriptive text. To complete the investigation, the researcher uses the qualitative approach. Students' mistakes affect the descriptive English content. Twenty junior high school students from west Jakarta were given writing prompts. Their text demonstrates how their sentences lost all of their original meaning. When asked to create an English descriptive text, they encountered challenges. Following an investigation of the students' English descriptive texts, twenty errors have occurred in the simple present tense; error of omission, error of selection, error of addition and error of ordering.